Dynamic simulation model of a biomimetic robotic fish with multi-joint propulsion mechanism - Korkmaz, Deniz; Akpolat, Z. Hakan; Soyguder, Servet; Alli, Hasan (Sage Publications Ltd, 2015)
In this paper, a biomimetic carangiform robotic fish is analysed based on dynamic and kinematic models. The carangiform fish can swim with features like high mobility, fast swimming and changing direction suddenly. Because it has these amazing features, a carangiform swimmer is modelled. Dynamic and kinematic models are analytically obtained to design a biomimetic carangiform robotic fish. The designed robotic fish consists of two parts: an anterior rigid body and a flexible tail, which is modelled as a four-joint propulsion mechanism, and each joint is driven by a servo motor. The dynamic model is developed in the MATLAB/Simulink environment using a Lagrange function and the state-space model is performed to linearize the obtained model. Each joint is controlled with conventional PID controller in the simulation. Furthermore, a solid model of the robotic fish prototype is drawn in SolidWorks and transferred to the MATLAB/Simmechanics environment, and the motion of the robotic fish is simulated using joint angles. Finally, experimental studies and simulation results show that a carangiform motion for autonomous swimming is developed and verified using controlled joint angles.
Keywords: Biomimetic design; dynamic modelling; Lagrange method; multi-joint actuation; robotic fish